Aberrant trafficking of hepatitis B virus glycoproteins in cells in which N-glycan processing is inhibited - Lu, Xuanyong (The National Academy of Sciences of the USA, 1997)
The role of N-glycan trimming in glycoprotein fate and function is unclear. We have recently shown that hepatitis B virus (HBV) DNA is not efficiently secreted from cells in which α-glucosidase mediated N-glycan trimming is inhibited. Here it is shown that, in cells in glucosidase-inhibited cells, viral DNA, accompanied by envelope and core proteins, most likely accumulate within lysosomal compartments. Pulse–chase experiments show that although the viral glycoproteins (L, M, and S) are dysfunctional, in the sense that they do not mediate virion egress and are not efficiently secreted from the cell, they all still leave the endoplasmic reticulum (ER). Surprisingly, however, the glycoproteins retained within the cell were not rapidly degraded, appearing as aggregates, enriched for L and M, with intracellular half-lives exceeding 20 h. Moreover, by 24 h after synthesis, a substantial fraction of the detained glycoproteins appeared to return to the ER, although a considerable amount was also found in the lysosomes. To our knowledge, this is the first report that shows, as a consequence of inhibiting glycosylation processing, certain glycoproteins (i) become dysfunctional and aggregate, yet still depart from the ER, and (ii) have extended rather than shortened half-lives. Taken together, these data suggest that proper intracellular routing of HBV glycoproteins requires ER glucosidase function. It is hypothesized that failure to process N-glycan causes HBV glycoproteins to aggregate and that impaired protein–protein interactions and trafficking are the result of misfolding.